2017
DOI: 10.5430/jnep.v7n8p86
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for supporting a pregnant patient with brain death: A case discussion and literature review

Abstract: Brain death implies irreversible cessation of brainstem function. While it is generally considered unethical and futile to support vital organs once brain death is diagnosed, patients who are both pregnant and brain dead complicate this issue. The appropriateness of continuing maternal somatic support to prolong gestation until delivery is an issue of debate. This paper reviews the literature and opens dialogue about the need for guidelines and recommendations in anesthesia care, including the ethics, legality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…Therefore, this treatment can be considered experimental and needs to respect ethical and institutional requirements to proceed, and as such, adequate assessment of the condition of the fetus (ultrasonography examination and cardiotocography) should be evaluated for an informed decision to be made, and informed consent from the father of the child, next of kin, or family should be obtained . In order to make an informed decision, a meeting of the interdisciplinary team needs to be organized, consisting of physicians, the caregiving team, the hospital ethics committee, and members of the family . Such a meeting would involve discussion of fetal prognosis, delivery prospects, and the potential emotional and financial factors of the prolonged corporeal support, which would need to be followed up with adequate and extensive counseling .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, this treatment can be considered experimental and needs to respect ethical and institutional requirements to proceed, and as such, adequate assessment of the condition of the fetus (ultrasonography examination and cardiotocography) should be evaluated for an informed decision to be made, and informed consent from the father of the child, next of kin, or family should be obtained . In order to make an informed decision, a meeting of the interdisciplinary team needs to be organized, consisting of physicians, the caregiving team, the hospital ethics committee, and members of the family . Such a meeting would involve discussion of fetal prognosis, delivery prospects, and the potential emotional and financial factors of the prolonged corporeal support, which would need to be followed up with adequate and extensive counseling .…”
Section: Discussionmentioning
confidence: 99%
“…The growing number of cases has motivated researchers to present them in systematic reviews, demonstrating in the first review 11 reported cases of brain death in pregnancy (BDP) for the period from 1979 to 2000 . The second systematic review presented 30 cases dating from 1982 to 2010, and, finally, a more recent one involved 43 cases, including two where the mother was in a vegetative state, for the period from 1979 to 2015 . Additionally, in the literature the medical and ethical management of pregnancies in a vegetative state is very often equated with the BDP.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations